'By What Right does the Scalpel Enter the Pauper's Corpse?' Dissections and Consent in Late Nineteenth-Century Belgium. (15th May 2017) - Claes, Tinne
Summary: In the nineteenth century, the distribution of corpses to anatomists was based on a reciprocal logic. In exchange for state-funded care, the poor subordinated their bodies to the advancement of science. Recent research has shown that this practice was increasingly contested in continental Europe from the late nineteenth century onwards. In this article, the Belgian debate on dissection without consent is scrutinised from multiple perspectives. I argue that political and legal debates on the treatment of the poor and the ownership of the dead led to changes in the distribution of corpses for dissection. As indigent patients obtained ownership of their bodies, anatomists increasingly had to comply with the standard of consent. By contextualising the emergence of anatomical donation, this article sheds light on a neglected topic in the social history of anatomy and on the changing significance of death customs, which began to express the will of the deceased.